2022
DOI: 10.3390/ijms232012552
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Method for Producing oxLDL: Characterization of Their Effects on HPV-Positive Head and Neck Cancer Cells

Abstract: Cardiovascular diseases (CVD) and cancers are the two main causes of death worldwide. The initiation and progression of atherosclerosis is, in large part, caused by oxidized low-density lipoproteins (oxLDL); interestingly, oxLDL may also play a role in cancer cell metabolism and migration. As oxLDL are generally obtained by tedious ultracentrifugation procedures, “home-made” oxLDL were obtained by (i) applying a purification kit to isolate LDL and VLDL from human plasma; (ii) isolating LDL from VLDL by gel per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…LOX-1 receptor and oxLDLs are associated with the development and progression of several pathologies, such as atherosclerosis, obesity, type 2 diabetes, and different cancers [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Notably, in CaP, we have previously shown that LOX-1 activation by oxLDLs stimulates tumor angiogenesis [ 31 ], epithelial-mesenchymal transition, and tumorigenic potential, being determinant for tumor growth [ 32 ], which could explain why obese patients with CaP progress to more malignant stages in a shorter period of time compared to patients with average weight [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LOX-1 receptor and oxLDLs are associated with the development and progression of several pathologies, such as atherosclerosis, obesity, type 2 diabetes, and different cancers [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Notably, in CaP, we have previously shown that LOX-1 activation by oxLDLs stimulates tumor angiogenesis [ 31 ], epithelial-mesenchymal transition, and tumorigenic potential, being determinant for tumor growth [ 32 ], which could explain why obese patients with CaP progress to more malignant stages in a shorter period of time compared to patients with average weight [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of LOX-1 and oxLDLs is not only restricted to pathologies, such as atherosclerosis or endothelial dysfunction, but has also been associated with the progression of chronic pathologies, such as obesity [ 18 , 19 ], type II diabetes mellitus [ 20 , 21 ], and various types of cancer. The role of LOX-1 in cancer is related to the hallmarks of cancer, such as angiogenesis, invasion, metastasis, resisting cell death, and sustained proliferative signaling between others [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], and has been addressed in depth in several reviews [ 20 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to investigate the influence of oxLDL on human umbilical vein endothelial cells (HUVECs) and on human leukaemia monocytic cell line (THP-1), we used our "homemade" oxLDL, where we isolated and oxidated LDL using our previously described protocol [27]. LDL and VLDL were first isolated from human plasma by serial precipitation and centrifugation steps.…”
Section: Oxldl Productionmentioning
confidence: 99%
“…LDL were separated from VLDL by high-performance liquid chromatography in an aqueous size-exclusion chromatography column. Then, LDL was oxidated by 5 µM CuSO 4 incubation while agarose gel electrophoresis was assessed to control the quality of the oxidation [27].…”
Section: Oxldl Productionmentioning
confidence: 99%